UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE NUMBER HEAD TOGETHER PADA SISWA KELAS III SDN 38/II PAUH AGUNG - Puput Wahyu Hidayat; NURLEV AVANA; RITA SUMARTI (LP3M STKIP Muhammadiyah Muara Bungo, 2021)
The background of this research is the low student learning outcomes caused by an inappropriate learning approach. The process carried out in the classroom is also not pleasant, causing the learning outcomes and learning process of students in class III of SD Negeri No.38/II Pauh Agung to be low. So with this problem, the researchers conducted research using the Number Head Together model. This type of research is classroom action research which consists of four stages, namely planning, action, observation and reflection, which is carried out collaboratively between practitioners and observers. The research was conducted in SD Negeri No. 38/II Pauh Agung. The subjects of this study were 20 third grade students. The research was carried out for 2 cycles. Each cycle consists of 2 meetings. Data collection techniques using the test method, observation sheets and documentation. Data analysis techniques are descriptive qualitative and quantitative.